THE INFLUENCE OF FLIGHT CONFIGURATION, CAMERA CALIBRATION, AND GROUND CONTROL POINTS FOR DIGITAL TERRAIN MODEL AND ORTHOMOSAIC GENERATION USING UNMANNED AERIAL VEHICLES IMAGERY - Garcia, Marcos Vinícius Yodono; Oliveira, Henrique Cândido de (Boletim de Ciências Geodésicas, 2022)
Technological improvement in sensors and the use of computer vision algorithms made possible the generation of high accuracy mapping products (cm level) using data acquired by low-cost Unmanned Aerial Vehicles (UAV). However, the procedure to optimally set the aerial block configuration is not well understood for some users mainly due to the popularization of the UAV and its use by non-specialists. This study aims to contribute to this aspect, investigating and highlighting the influence of flight parameters, camera calibration and number of Ground Control Points (GCP) on generating digital terrain models and orthomosaic. To address this issue, several field experiments and data processing were carried out. The quality was assessed by calculating the Root Mean Square Error (RMSE) together with a bias evaluation (t-Student test at 90% confidence level). The results suggest that an optimum block configuration for accurate and unbiased products is achieved by surveying at rates of 80%/60% (forward and sidelap, respectively), with an average Ground Sample Distance (GSD) of around 1 cm at a flight height of 31 m, using a precalibrated camera and 5 GCP at least.